EMC Certification of a Digital Radio Astronomy Receiver: A Case Study - Schlagenhaufer, Franz; Crosse, Brian; Emrich, David; Tingay, Steven; Hall, Peter (IEEE, 2012)
This paper outlines the challenge of practical EMC measurements on a large electronic system destined for a radio astronomy observatory. The digital receiver package of the Murchison Widefield Array (MWA) is used as a case study and progress towards meeting what is probably one of the world's most stringent EMC requirement is described